Single-Stage Endoscopic Stone Extraction and Cholecystectomy during the Same Hospitalization - Terauchi, Toshiaki (Clin Endosc, 2019)
BACKGROUND/AIMS: The clinical impact of single-stage endoscopic stone extraction by endoscopic retrograde cholangiopancreatography (ERCP) and cholecystectomy during the same hospitalization remains elusive. This study aimed to determine the efficacy and safety of single-stage ERCP and cholecystectomy during the same hospitalization in patients with cholangitis. METHODS: We retrospectively reviewed the medical records of 166 patients who underwent ERCP for mild to moderate cholangitis due to choledocholithiasis secondary to cholecystolithiasis from 2012 to 2016. RESULTS: Complete stone extraction was accomplished in 92% of patients (152/166) at the first ERCP. Among 152 patients who underwent complete stone extraction, cholecystectomy was scheduled for 119 patients (78%). Cholecystectomy was performed during the same hospitalization in 89% of patients (106/119). We compared two groups of patients: those who underwent cholecystectomy during the same hospitalization (n=106) and those who underwent cholecystectomy during a subsequent hospitalization (n=13). In the delayed group, cholecystectomy was performed about three months after the first ERCP. There were no significant differences between the groups in terms of operative time, rate of postoperative complications, and interval from cholecystectomy to discharge. CONCLUSIONS: Single-stage endoscopic stone extraction is recommended in patients with mild to moderate acute cholangitis due to choledocholithiasis. The combination of endoscopic stone extraction and cholecystectomy during the same hospitalization is safe and feasible.